2019
DOI: 10.1097/aln.0000000000002482
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and End-tidal Carbon Dioxide Ranges during Aneurysm Occlusion and Neurologic Outcome after an Aneurysmal Subarachnoid Hemorrhage

Abstract: EDITOR’S PERSPECTIVE What We Already Know about This Topic It remains unknown what end-tidal carbon dioxide and mean arterial pressure are optimal for surgical management of patients with an aneurysmal subarachnoid hemorrhage What This Article Tells Us That Is New The investigators retrospectively evaluated 1,099 patients who had endovascular coiling or surgical clipping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Regarding ETCO 2 , we found no statistically significant difference between the DNID and non-DNID groups (p > 0.05). Our ETCO 2 result was similar to Akkermans et al [6] that showed no association between ETCO 2 and the development of DNID with an adjusted risk ratio of 0.95 (95% CI 0.81-1.10; p < 0.496) for ETCO 2 less than 30 mmHg. However, the lowest point of ETCO 2 in our study is observed at 27 mmHg that yields a sensitivity of 78.6% and specificity of 35.7%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding ETCO 2 , we found no statistically significant difference between the DNID and non-DNID groups (p > 0.05). Our ETCO 2 result was similar to Akkermans et al [6] that showed no association between ETCO 2 and the development of DNID with an adjusted risk ratio of 0.95 (95% CI 0.81-1.10; p < 0.496) for ETCO 2 less than 30 mmHg. However, the lowest point of ETCO 2 in our study is observed at 27 mmHg that yields a sensitivity of 78.6% and specificity of 35.7%.…”
Section: Discussionsupporting
confidence: 89%
“…However, recommendations for the target point of appropriate blood pressure during surgery vary [2]. However, in contrast to that mentioned above, a recent retrospective observational study found that hypotension and hypertension during aneurysm occlusion were not associated with a poor neurological outcome in aneurysmal subarachnoid hemorrhage patients [6]; therefore, this issue remains controversial. In addition, hypocapnia is another factor that may induce cerebral vasoconstriction and causing brain ischemia [7].…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, it is plausible that high-normal P a CO 2 values may have a different effect on outcome than lownormal values. Another recent study focused on endtidal CO 2 values during the coiling or clipping procedure and found no association with clinical outcome [24]. The results of this study imply that P a CO 2 values might have to be studied for a longer period of time and not only for the time of intervention / surgery.…”
Section: Introductionmentioning
confidence: 61%
“…demonstrate the importance of a standardised intraoperative blood pressure management with regards to the postoperative neurological outcome in their recent retrospective observational study. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%